Crystal structure of catena-poly[diaqua-bis(μ2-4,4′-bipyridyl-κ2N:N′) disilver(I)] 4-oxidopyridine-3-sulfonate trihydrate, C25H29Ag2N5O9S - Zhao Han-Lin; Jiang Jin-Ke; Jiang Hui; Dong Xian-Wu; Li Xue (Zeitschrift für Kristallographie - New Crystal Structures)
C25H29Ag2N5O9S, monoclinic, P21/m (no. 11), a = 8.5437(16) Å, b = 17.852(4) Å, c = 9.3335(13) Å, β = 101.380(16)°, V = 1395.6(5) Å3, Z = 2, Rgt(F) = 0.0271, wRref(F2) = 0.0653, T = 293(2) K.